A development plan for the Reading Center at Barangay Pundaquit, San Antonio, Zambales - Ventura, Aries Joy T.
Throughout the years, establishing public libraries have been a longtime phenomenon initiated by professionals in the field of Library and Information Science (LIS). However, like the profession itself, public libraries have been pursuant of justifying their societal and economic value for the people in the communities it is meant to serve.